PERSEPSI GURU PADA KESESUAI ISI PADA BUKU KURIKULUM MERDEKA SD NEGERI 2 LAKEA - Herlina; Hasia Marto; Nasriani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the impact of anti-bullying socialization on student attitudes at State Elementary School 3 Karamat. Bullying is a serious problem that requires an evaluation of the effectiveness of intervention programs. This research employed a qualitative method conducted at SD Negeri 3 Karamat, with teachers and the head of school as research subjects. Data collection techniques included observation, interviews, and documentation. The results indicate that the anti-bullying socialization had a significant positive impact on student attitudes. This positive change was confirmed across three main indicators: (1) daily behavior, (2) response to social situations, and (3) participation in school activities. Therefore, it can be concluded that the implemented socialization program was effective in shaping and enhancing students' positive attitudes towards the issue of bullying.